The Dwarf Irregular Galaxy NGC 6822. II. Young, Intermediate and Old Stellar Populations: Comparison between Theory and Observations - Maria Tantalo; Giuseppe Bono; Maurizio Salaris; Adriano Pietrinferni; Matteo Monelli; Michele Fabrizio; Vittorio F. Braga; Annalisa Calamida; Massimo Dall’Ora; Valentina D’Orazi; Ivan Ferraro; Giuliana Fiorentino; et al. (The Astrophysical Journal)
This paper presents a quantitative analysis of the stellar content in the Local Group dwarf irregular galaxy NGC 6822 by comparing stellar evolution models and observations in color–magnitude diagrams (CMDs) and color–color diagrams (CC-Ds). Our analysis is based on optical ground-based g , r , i photometry, and deep archival Hubble Space Telescope photometry of two fields in the galactic disk. We compared young, intermediate-age, and old stellar populations with isochrones from the BaSTI-IAC library and found that NGC 6822 hosts a quite metal-rich ([Fe/H] = −0.7 to −0.4) young component with an age ranging from 20–100 Myr. The intermediate-age population experienced a modest chemical enrichment between 4 and 8 Gyr ago, while stars older than 11 Gyr have a low metal abundance ([Fe/H] ∼ −1.70). We also identified the asymptotic giant branch (AGB) clump population with a luminosity peak at i ∼ 23.35 mag. Our analysis of both the CMD and the optical–near-IR (NIR)–mid-IR (MIR) CC-Ds of AGB oxygen- and carbon-rich stars, using the PARSEC+COLIBRI isochrones with and without circumstellar dust, reveals that this stellar component exhibits a spread in age from 1–2 Gyr and in metallicity between [Fe/H] = −1.30 and −1.70. The stellar models we used reproduce very well the two distinct color sequences defined by AGB O- and C-rich stars in the various optical–NIR–MIR CC-Ds, suggesting that they are reliable diagnostics to identify and characterize intermediate-age stellar populations. However, we also find that evolutionary prescriptions in the optical i -( r − i ) CMDs predict, at fixed color, systematically lower luminosities than observed AGB stars.